Exploitation of Skin Microbiota in Wound Healing: Perspectives During Space Missions - Marvasi, Massimiliano; Monici, Monica; Pantalone, Desirée; Cavalieri, Duccio (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing is slowed in Space. Microgravity and possible physical factors associated with Space affect alterations in fibroblast, matrix formation, dysregulation in apoptosis and inflammation. The microbial populations settled on skin, space modules, in space suits, are also playing a pivotal role, as wound healing is also affected by the microbial community. We propose a perspective that includes four domines for the application of human skin microbiota for wound healing in Space: The natural antimicrobial properties of the skin microbiota, the crosstalk of the skin microbiota with the immune system during wound healing, the contribution of the microbiota in precision medicine in wound healing, and the role of gut-skin and gut-brain axes. A stronger understanding of the connections and metabolic network among bacteria, fungi, the host’s immune system and the host metabolism will support the basis for a better wound healing in Space.